2019
DOI: 10.1016/j.heliyon.2019.e01509
|View full text |Cite
|
Sign up to set email alerts
|

Dual phototransformation of the pollutants methyl orange and Cr (VI) using phthalocyanine-cobalt ferrite based magnetic nanocomposites

Abstract: Bifunctional nanocomposites based on zinc phthalocyanines and glutathione capped CoFe 2 O 4 magnetic nanoparticles (GSH-CoFe 2 O 4 MNPs) are applied in a binary system wherein simultaneous photooxidation of methyl orange (MO) and photoreduction of Cr (VI) are conducted. The photoactivity of two zinc Pcs with different functional moieties are compared based on their interactions with GSH-CoFe 2 O … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 64 publications
2
2
0
Order By: Relevance
“…The amorphous nature of GSH@SNP was further confirmed by powder XRD studies (Figure i), where a broad peak at a 2θ value of ∼22° was observed for GSH@SNP. The peaks at 2θ values of ∼35, 43, 52, and 57° correspond to 311, 400, 422, and 511 planes for GSH@SNP, respectively. , Similar results were also obtained for Cyst@SNP and Cys@SNP (Figure S3). In literature, SNPs are known to be either mesoporous or microporous .…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…The amorphous nature of GSH@SNP was further confirmed by powder XRD studies (Figure i), where a broad peak at a 2θ value of ∼22° was observed for GSH@SNP. The peaks at 2θ values of ∼35, 43, 52, and 57° correspond to 311, 400, 422, and 511 planes for GSH@SNP, respectively. , Similar results were also obtained for Cyst@SNP and Cys@SNP (Figure S3). In literature, SNPs are known to be either mesoporous or microporous .…”
Section: Resultssupporting
confidence: 81%
“…The peaks at 2θ values of ∼35, 43, 52, and 57°correspond to 311, 400, 422, and 511 planes for GSH@SNP, respectively. 31,32 Similar results were also obtained for Cyst@SNP and Cys@SNP (Figure S3). In literature, SNPs are known to be either mesoporous or microporous.…”
Section: Chemical and Morphologicalsupporting
confidence: 82%
“…After coating, the nanocomposites presented lower aggregation, slightly larger particle size, and a smoother surface, which may be due to the presence of F127 on the surface of the MNPs. In addition, the obtained nanocomposites were found to be increased in the range of 50–100 nm, due to the aggregation produced by their magnetic properties [ 64 , 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…Since environmental pollution is a vital detrimental factor for human health, finding a suitable solution is imperative. Dyes are prominent pollutants that pose serious dangers to humans, other animals, and living organisms as they are not degraded by aerobic treatment processes and therefore their removal from industrial wastewater before discharge requires considerable care 7 . These pigments mainly contain one or more benzene rings, which are very toxic and their late decomposition can be carcinogenic, and if left untreated, they can enter the environment and cause irreparable damage to the environment 8–15 .…”
Section: Introductionmentioning
confidence: 99%